Exploring Roblox as a Social Learning Environment for EFL Vocabulary Learning - Zikrina; Edi; Irwandi (JADEs Journal of Academia in English Education, 2026)
This study examines Roblox as an informal social learning environment for the development of English vocabulary among EFL (English as a Foreign Language) students in Indonesia. Using a descriptive qualitative design, data were collected from 35 active Roblox users via open-ended questionnaires, supplemented by field notes and interviews, and analyzed using inductive thematic analysis. The analysis identified key themes, including contextual vocabulary acquisition, willingness to communicate, socially mediated learning strategies, linguistic challenges, and informal learning orientation, as well as three learner profiles: language-focused learners, hybrid learners, and incidental learners. The findings suggest that vocabulary acquisition occurs through contextual use, repetition, and the negotiation of meaning during authentic interactions, rather than through explicit instruction. Participants reported increased confidence and reduced anxiety, as the non-evaluative environment encouraged spontaneous communication. Although the use of slang and fast-paced interactions initially posed challenges, participants learned to adapt by interpreting meaning from context, modelling their peers, and using strategies such as asking for clarification. These processes enabled sustained interaction and supported the development of resilience in communication.